Corrosion-resistant integrated composite material bipolar plate for flow battery and preparation method of corrosion-resistant integrated composite material bipolar plate
The corrosion-resistant integrated composite bipolar plate for liquid flow batteries was prepared through co-extrusion technology, which solved the electrochemical corrosion problem of the bipolar plate in the liquid flow channel area in the flow guide frame, achieved corrosion resistance and efficient conduction of the bipolar plate, and improved the stability and service life of the stack.
Patent Information
- Application Number
- CN202411627868.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-11
AI Technical Summary
The existing flow battery bipolar plates are difficult to resist electrochemical corrosion in the inlet and outlet of the flow channel of the flow frame, resulting in electrochemical corrosion and electrolyte series liquid problems, affecting the efficiency and service life of the stack.
Co-extrusion technology is used to prepare corrosion-resistant integrated composite bipolar plates. By setting corrosion-resistant areas on both sides of the bipolar plate lengthwise and combining the intermediate conductive reaction zone, the electrochemical corrosion resistance and intermediate conductive functions on both sides of the bipolar plate are realized.
The stack structure and production process are simplified, the stack quality stability and service life are improved, the electrolyte series liquid problem caused by electrochemical corrosion is avoided, and the corrosion resistance and conductivity of the bipolar plate are enhanced.
Smart Images

Figure CN119601700A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of vanadium flow batteries, and in particular relates to a corrosion-resistant integrated composite material bipolar plate for a flow battery and a preparation method thereof. Background Art
[0002] Economic progress has led to a continuous increase in energy demand, while the widespread consumption of fossil fuels has caused a series of environmental problems. In order to ensure energy security and achieve sustainable development, countries around the world have adopted strategies to use renewable energy on a large scale and achieve energy diversification; however, the instability and discontinuity of renewable energy such as wind and solar energy have brought challenges to their application. Therefore, the use of energy storage technology to ensure the continuous supply of renewable energy has become the key to solving this problem. In the current large-scale energy storage market, flow batteries are regarded as one of the technologies with the most development potential due to their flexible design, high safety and long design life.
[0003] The bipolar plate is one of the key parts of the flow battery. It mainly serves to separate the positive and negative electrolyte solutions, collect current and support the electrodes. It has high requirements for conductivity, liquid resistance, electrochemical stability and certain mechanical strength. Bipolar plates are generally divided into graphite bipolar plates, metal bipolar plates and carbon-plastic composite bipolar plates. The mechanical properties of graphite bipolar plates are not satisfactory and cannot meet the standards for battery stack assembly. Metal bipolar plates are expensive and cannot be used on a large scale. Traditional carbon-plastic composite bipolar plates are single conductive bipolar plates. Liquid flow batteries require bipolar plates and liquid flow battery guide frame inlet and outlet channels ( Figure 7 ) The corresponding area must be resistant to electrochemical corrosion, otherwise the bipolar plate in this area will be electrochemically corroded and damaged, and then the positive and negative electrolytes will cross-link, affecting the efficiency and service life of the battery stack. Traditional graphite bipolar plates and carbon-plastic composite bipolar plates are both single conductive bipolar plates, which cannot simultaneously meet the functions of conductivity in the middle part and electrochemical corrosion resistance of the bipolar plates corresponding to the inlet and outlet flow channel areas of the guide frame. To meet the above requirements, it is usually practice to separately set corrosion-resistant plates in the inlet and outlet flow channel areas of the guide frame by splicing or bonding. This improved process increases the complexity of the battery stack structure and processing technology, affecting the quality stability and service life of the battery stack. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a corrosion-resistant integrated composite bipolar plate for a liquid flow battery and a preparation method, which greatly simplifies the battery stack structure, reduces the complexity of the battery stack production process, thereby improving the quality stability and service life of the battery stack, and solves the problem that the existing bipolar plates need to be spliced or bonded to achieve electrochemical corrosion resistance in the inlet and outlet liquid flow channel areas of the bipolar plates and the guide frame.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is: A method for preparing a corrosion-resistant integrated composite material bipolar plate for a flow battery is provided, comprising the following steps: S1: Prepare the materials for the reaction zone of the bipolar plate: add 10-50wt% of thermoplastic polymer material and 30-70wt% of conductive carbon material in proportion, mix and put into an oven for drying, add into an internal mixer, and then add 0.5-2wt% of additives for internal mixing to obtain a first intermediate material; S2: Prepare the material for the anti-corrosion zone of the bipolar plate: add 10-50wt% of thermoplastic polymer material and 50-70wt% of anti-corrosion filler in proportion, mix and put into an oven for drying, add into an internal mixer, and then add 0.5-2wt% of additives for internal mixing to obtain a third intermediate material; S3: Crushing and granulating: crushing the first intermediate material and the third intermediate material into granular materials of 0-10 mm in a crusher respectively, removing impurities in the crushed materials through an impurity separator, and obtaining the second intermediate material and the fourth intermediate material respectively; S4: Melt extrusion: Add the second intermediate material and the fourth intermediate material into the first extruder and the second extruder respectively, and adjust the temperature of the barrel area, flow channel area, distributor and co-extrusion die of the first extruder and the second extruder to fully melt the second intermediate material and the fourth intermediate material and further mix them evenly; S5: Co-extrusion molding: After being fully melted, the second intermediate material and the fourth intermediate material enter the co-extrusion die through their respective distributors, are extruded through the lip of the co-extrusion die for thickness and width distribution, and are calendered at a three-roll calender to obtain the fifth intermediate material; S6: Sheet forming: The fifth intermediate material passes through a traction machine, a trimming machine and a cutting machine in sequence to obtain an integrated bipolar plate resistant to electrochemical corrosion on both sides.
[0006] The beneficial effects of adopting the above technical solution are: by adding thermoplastic polymer materials, conductive carbon materials and other reaction zone materials supporting the bipolar plate in proportion to S1, the thermoplastic polymer material serves as a raw material matrix to provide mechanical strength and corrosion resistance support for the conductive zone bipolar plate, the conductive carbon material improves the conductivity of the bipolar plate, and drying can remove moisture from the reaction zone raw materials. Mixing and mixing can make the raw materials mix evenly, and the additives can improve other processing properties such as the fluidity of the bipolar plate, so that the thermoplastic polymer material and the conductive carbon material can be mixed more evenly, thereby ensuring the isotropy of the first intermediate material.
[0007] In S2, thermoplastic polymer materials and anti-corrosion fillers are added in proportion, and the addition ratio of anti-corrosion fillers is 50~70wt%, which effectively improves the electrochemical corrosion resistance of the anti-corrosion zone. The synergistic effect of anti-corrosion fillers, thermoplastic polymer materials and additives can also ensure the performance stability of the anti-corrosion zone.
[0008] In S3, the first intermediate material and the second intermediate material are crushed into 0-10 mm granular materials by a crusher, and impurities are removed by an impurity separator, thereby improving the purity and uniformity of the materials and facilitating the continuity and stability of subsequent material extrusion.
[0009] In S4, the crushed first intermediate material and the second intermediate material are added to the first extruder and the second extruder respectively, and the second intermediate material and the fourth intermediate material are fully melted and further mixed evenly by adjusting the temperatures of the barrel area, flow channel area, distributor and co-extrusion die of the first extruder and the second extruder, thereby ensuring the melting state and quality of the materials during extrusion.
[0010] In S5, the first intermediate material and the second intermediate material of the anti-corrosion zone are simultaneously extruded through the co-extrusion die, and stably form an integrated bipolar plate structure with a middle conductive reaction zone and anti-corrosion zones on both sides. By adjusting the lip gap of the co-extrusion die, the preforming of the bipolar plate can be achieved, and then by adjusting the roller distance between the middle and lower rollers, the fifth intermediate material of the continuous plate material that meets the required thickness, reaction zone and anti-corrosion zone width is finally obtained. After cooling and forming, the functional requirements of the integrated bipolar plate being conductive in the middle part and resistant to electrochemical corrosion on both sides are achieved.
[0011] In S6, the pulling speed of the traction machine is adjusted, and the traction machine pulls the fifth intermediate material prepared by the three-roll calender to make the surface of the bipolar plate smoother, thereby improving the overall flatness of the bipolar plate; by adjusting the cutter distance, the bipolar plate of the required width is cut out; the traction of the traction machine can ensure the continuous output and stable transmission of the bipolar plate, while the trimmer and the cutter can trim and cut the calendered bipolar plate to obtain an integrated bipolar plate that meets the length, width and thickness required for production.
[0012] The integrated bipolar plate produced by co-extrusion technology can eliminate the production process of bipolar plate splicing or bonding, simplify the production process of liquid flow battery stacks and improve production efficiency; in addition, the simplification of the stack structure and production process also helps to improve the quality stability and efficiency of the stack products; at the same time, the integrated bipolar plate combines the highly conductive reaction zone and the corrosion-resistant anti-corrosion zone, so that the same bipolar plate has both a highly conductive reaction zone and a corrosion-resistant zone resistant to electrochemical corrosion. It can be widely used in all-vanadium liquid flow batteries, zinc-bromine liquid flow batteries and other liquid flow batteries, with better economic and promotion benefits.
[0013] Furthermore, the melt flow index of the thermoplastic polymer material in S1 is 1 to 50 g / 10 min.
[0014] The beneficial effects of adopting the above technical solution are: by adopting a thermoplastic polymer material with a melt flow index of 1 to 50 g / 10 min, while improving the fluidity of the bipolar plate, the generation of defects such as bubbles and impurities is reduced, thereby ensuring the mechanical strength of the bipolar plate, thereby improving the consistency and quality of the bipolar plate during production.
[0015] Furthermore, the thermoplastic polymer material in S1 and S2 includes at least one of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyoxymethylene, carbonate, polyamide, acrylic plastic, polyolefin and copolymers thereof, polyphenylene ether and chlorinated polyether.
[0016] The beneficial effects of adopting the above technical solution are as follows: polyethylene and polypropylene have good processing performance and corrosion resistance. Different thermoplastic polymer materials are selected according to actual needs, which can not only ensure the processing performance of the bipolar plate, but also enhance its corrosion resistance and mechanical strength, and can also reduce production costs, reduce environmental pollution and resource waste, and have better practicality and economic benefits.
[0017] Furthermore, the conductive carbon material in S1 includes at least one of carbon black, graphite, carbon fiber, graphene and carbon nanotubes.
[0018] The beneficial effects of adopting the above technical solution are: the rational use of conductive carbon materials such as carbon black and graphite can not only improve the overall conductivity of the bipolar plate, but also improve the conductive uniformity of the bipolar plate. By rationally selecting different conductive carbon materials, it is possible to balance the conductivity and mechanical properties of the bipolar plate and control the production cost.
[0019] Furthermore, the additives in S1 and S2 include at least one of paraffin wax, polyethylene wax, chlorinated paraffin, polyacrylamide, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, cellulose derivatives, guar gum and polyethylene glycol esters of fatty acids.
[0020] The beneficial effects of adopting the above technical scheme are as follows: when preparing the raw materials of the reaction zone, additives are added, and the additives can play a role in lubrication, dispersion and flow promotion, reduce friction and resistance, and improve the smoothness during melt extrusion; and when preparing the raw materials of the anti-corrosion zone, additives are added, and the additives can enhance the density. Through the action of the additives and the anti-corrosion fillers, the anti-corrosion performance of the anti-corrosion zone is further improved, avoiding the problem of liquid cross-linking in the bipolar plate due to electrochemical corrosion.
[0021] Furthermore, the anti-corrosion filler in S2 includes at least one of insulating carbon black, white carbon black, carbon fiber and glass fiber.
[0022] The beneficial effects of adopting the above technical scheme are as follows: anti-corrosion fillers such as carbon black, white carbon black, carbon fiber and glass fiber have good corrosion resistance, can effectively avoid electrochemical corrosion, extend the service life of the bipolar plate, and improve the overall performance of the fuel cell stack; in addition, by compounding the anti-corrosion filler with thermoplastic polymer materials and additives to form an anti-corrosion zone, the integrated production of corrosion protection on both sides of the bipolar plate and conductivity in the middle can be achieved, which greatly simplifies the production process of the bipolar plate, reduces production costs, and improves production efficiency.
[0023] Furthermore, the mixing temperature of the internal mixers in S1 and S2 is 170-250° C., and the mixing time is 10-60 min.
[0024] The beneficial effects of adopting the above technical solution are as follows: by adopting a mixing process with a mixing temperature of 170~250℃ and a mixing time of 10~60min, it can ensure that raw materials such as thermoplastic polymer materials, conductive carbon materials, additives and anti-corrosion fillers are fully mixed in the mixer and distributed more evenly, and the temperature of 170~250℃ is conducive to softening the raw materials, improving fluidity, and thereby improving the consistency and stability between the raw materials.
[0025] Furthermore, in S4, the barrel zone temperature of the first extruder and the second extruder is 160-200°C, the flow channel zone temperature is 200-240°C, the distributor temperature is 240-260°C, and the co-extrusion die head temperature is 220-260°C.
[0026] The beneficial effects of adopting the above technical solution are: by setting a suitable temperature according to actual production, the extrusion efficiency and production efficiency can be improved, and the consistency and stability of the bipolar plate production can be ensured.
[0027] Furthermore, the lip thickness of the co-extrusion die head in S5 is 2-5 mm, the width of the middle area is 300-400 mm, and the width of the two side areas is 100-200 mm.
[0028] The beneficial effects of adopting the above technical scheme are as follows: by setting the thickness of the co-extrusion die lip at 2 to 5 mm, it helps to ensure the smoothness of the extrusion process, reduce extrusion resistance and energy consumption, and ensure the thickness consistency of the bipolar plate during extrusion; the width of the middle area corresponds to the width of the reaction zone, which can ensure that the reaction zone of the bipolar plate has sufficient area to collect current and support the motor, meeting the conductivity requirements of the liquid flow battery for the bipolar plate; the width of the two side areas corresponds to the width of the anti-corrosion zone, which can ensure that the bipolar plate has sufficient electrochemical corrosion resistance in the inlet and outlet liquid flow channel area of the guide frame, avoiding the problem of electrolyte cross-linking; by precisely controlling the thickness of the co-extrusion die lip and the width of the reaction zone and the anti-corrosion zone, the integrated production of anti-corrosion on both sides of the bipolar plate and conductivity in the middle can be achieved, which greatly simplifies the production process of the liquid flow battery stack and improves the quality stability and service life of the stack.
[0029] A corrosion-resistant integrated composite bipolar plate for a liquid flow battery manufactured by the above preparation method comprises a bipolar plate reaction zone and an anti-corrosion zone, wherein the anti-corrosion zone is arranged on both sides along the length direction of the bipolar plate reaction zone.
[0030] The beneficial effect of adopting the above technical solution is: by setting anti-corrosion zones on both sides of the bipolar plates in the length direction, electrochemical corrosion of the bipolar plates in the inlet and outlet flow channel areas of the flow battery guide frame is avoided, which affects the performance of the flow battery stack.
[0031] In summary, the corrosion-resistant integrated composite material bipolar plate for a flow battery and the preparation method thereof provided by the present invention have the following beneficial effects: (1) The bipolar plate in the present invention is manufactured in an integrated manner through co-extrusion technology, which is corrosion-resistant on both sides and conductive in the middle. This greatly reduces the complexity of the battery stack process and the instability of the bipolar plate structure and performance caused by traditional splicing and bonding, simplifies the production process of the liquid flow battery stack and the stability of the liquid flow battery, avoids the problem of electrolyte cross-linking caused by electrochemical corrosion, and improves the product quality and service life of the bipolar plate.
[0032] (2) The bipolar plate of the present invention is provided with anti-corrosion zones on both sides in the length direction, thereby improving the anti-corrosion performance of the bipolar plate, avoiding the risk of cross-linking of positive and negative electrolytes due to electrochemical corrosion in the long side areas on both sides of the bipolar plate, and extending the service life.
[0033] (3) The reaction zone of the bipolar plate in the present invention is composited with thermoplastic polymer materials, conductive carbon materials and additives, so that the reaction zone has both good conductivity and good mechanical strength.
[0034] (4) The bipolar plate preparation method of the present invention adopts co-extrusion technology to produce an integrated bipolar plate, which greatly simplifies the existing liquid flow battery stack production process, reduces production costs and complexity, improves the quality stability and stack efficiency of the stack product, and solves the problems of complex stack process and unstable structural performance caused by the splicing of existing bipolar plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a processing flow chart of the present invention; Figure 2 This is a flow chart of the bipolar plate processing equipment in the present invention; Figure 3 This is a flow chart of materials processed in the present invention; Figure 4 It is a schematic diagram of bipolar plate extrusion in the present invention; Figure 5 A top view of the integrated bipolar plate of the present invention; Figure 6 It is a left view of the integrated bipolar plate of the present invention; Figure 7This is a schematic diagram of the overall structure after the integrated bipolar plate and the flow battery guide frame are spliced in the present invention; Among them, 1. bipolar plate body; 2. reaction area; 3. anti-corrosion area; 4. guide frame; 5. laser welding area; 6. extruder; 7. co-extrusion die; 8. three-roll calender; 9. traction machine; 10. cutting machine. DETAILED DESCRIPTION
[0036] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0037] Example 1 like Figure 5 to Figure 7 As shown, the corrosion-resistant integrated composite bipolar plate for a liquid flow battery provided by the present invention comprises a bipolar plate body 1, the bipolar plate body 1 comprises a reaction zone 2 and an anti-corrosion zone 3, the anti-corrosion zone 3 is arranged along both sides of the length direction of the bipolar plate reaction zone 2, and the anti-corrosion zone 3 corresponds to the inlet and outlet flow channel area of the liquid flow battery guide frame 4 By setting the anti-corrosion zone 3 on both sides of the bipolar plate in the length direction, the electrochemical corrosion resistance of the bipolar plate is improved, the risk of cross-linking of positive and negative electrolytes due to electrochemical corrosion of the bipolar plate is avoided, and the service life is extended; and there is a laser welding area 5 between the bipolar plate anti-corrosion zone 3 and the guide frame 4, and the bipolar plate and the guide frame 4 are connected by laser welding. The laser welding process can ensure the mechanical strength of the welding point and improve the structural stability of the bipolar plate and the battery stack.
[0038] like Figure 1 to Figure 4 As shown, the method for preparing the above-mentioned integrated composite material bipolar plate comprises the following steps: S1: Prepare materials for the bipolar plate reaction zone 2: add 10-50wt% of thermoplastic polymer material and 30-70wt% of conductive carbon material in proportion, mix and put into an oven for drying, add into a mixer, and then add 0.5-2wt% of additives for mixing to obtain a first intermediate material; S2: Prepare the material for the anti-corrosion zone 3 of the bipolar plate: add 10-50wt% of thermoplastic polymer material and 50-70wt% of anti-corrosion filler in proportion, mix and put into an oven for drying, add into an internal mixer, and then add 0.5-2wt% of additives for internal mixing to obtain a third intermediate material; S3: Crushing and granulating: crushing the first intermediate material and the third intermediate material into granular materials of 0-10 mm in a crusher respectively, removing impurities in the crushed materials through an impurity separator, and obtaining the second intermediate material and the fourth intermediate material respectively; S4: Melt extrusion: Add the second intermediate material and the fourth intermediate material into the first extruder 6 and the second extruder 6 respectively, and adjust the temperature of the barrel area, flow channel area, distributor and co-extrusion die 7 of the first extruder 6 and the second extruder 6 to fully melt the second intermediate material and the fourth intermediate material and further mix them evenly; S5: Co-extrusion molding: After being fully melted, the second intermediate material and the fourth intermediate material enter the co-extrusion die 7 through their respective distributors, are extruded through the lip of the co-extrusion die 7 for thickness and width distribution, and are calendered at the three-roll calender 8 to obtain the fifth intermediate material; S6: Plate forming: The fifth intermediate material passes through a traction machine 9, a trimming machine and a cutting machine 10 in sequence to obtain an integrated bipolar plate with electrochemical corrosion resistance on both sides.
[0039] By adding thermoplastic polymer materials, conductive carbon materials and other materials supporting the reaction zone 2 of the bipolar plate in proportion to S1, the thermoplastic polymer material serves as a raw material matrix to provide mechanical strength and corrosion resistance support for the conductive zone bipolar plate, and the conductive carbon material improves the conductivity of the bipolar plate. Drying can remove moisture from the raw materials in the reaction zone 2, and mixing and mixing can make the raw materials mix evenly. The additives can improve other processing properties such as the fluidity of the bipolar plate, so that the thermoplastic polymer material and the conductive carbon material can be mixed more evenly, thereby ensuring the isotropy of the first intermediate material.
[0040] In S2, by adding thermoplastic polymer materials and anti-corrosion fillers in proportion, and the addition ratio of anti-corrosion fillers is 50~70wt%, the electrochemical corrosion resistance of anti-corrosion zone 3 is effectively improved. Through the synergistic effect of anti-corrosion fillers, thermoplastic polymer materials and additives, the performance stability of anti-corrosion zone 3 can also be ensured.
[0041] In S3, the first intermediate material and the second intermediate material are crushed into 0-10 mm granular materials by a crusher, and impurities are removed by an impurity separator, thereby improving the purity and uniformity of the materials and facilitating the continuity and stability of subsequent material extrusion.
[0042] In S4, the crushed first intermediate material and the second intermediate material are added to the first extruder 6 and the second extruder 6 respectively, and the second intermediate material and the fourth intermediate material are fully melted and further mixed evenly by adjusting the temperatures of the barrel area, flow channel area, distributor and co-extrusion die 7 of the first extruder 6 and the second extruder 6, thereby ensuring the melting state and quality of the materials during extrusion; in addition, the crushed first intermediate material and the second intermediate material are heated in stages in the extrusion barrel, thereby ensuring stable melting and sufficient mixing of the materials, thereby providing guarantee for uniform extrusion of the sheet.
[0043] In S5, the first intermediate material and the second intermediate material of the anti-corrosion zone 3 are simultaneously extruded through the co-extrusion die 7, and stably form an integrated bipolar plate structure with a middle conductive reaction zone 2 and anti-corrosion zones 3 on both sides. By adjusting the lip gap of the co-extrusion die 7, the preforming of the bipolar plate can be achieved, and then by adjusting the roller distance between the middle and lower rollers, the fifth intermediate material of the continuous plate material that meets the required thickness, width of the reaction zone 2 and the anti-corrosion zone 3 is finally obtained, thereby achieving the functional requirements of the integrated bipolar plate being conductive in the middle part and resistant to electrochemical corrosion on both sides.
[0044] In S6, the pulling speed of the pulling machine 9 is adjusted, and the pulling machine 9 pulls the fifth intermediate material prepared by the three-roll calender 8 to make the surface of the bipolar plate smoother, thereby improving the overall flatness of the bipolar plate; by adjusting the cutting knife distance, the bipolar plate of the required width is cut out; the pulling action of the pulling machine 9 can ensure the continuous output and stable transmission of the bipolar plate, and the trimmer and cutter 10 can trim and cut the calendered bipolar plate to obtain an integrated bipolar plate that meets the length, width and thickness required for production.
[0045] During implementation, the preferred usage ratio of the thermoplastic polymer material in S1 and S2 is 25-35wt%, and the melt flow index thereof is 1-50g / 10min, and the thermoplastic polymer material includes one or more of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyoxymethylene, carbonate, polyamide, acrylic plastic, polyolefin and its copolymer, polyphenylene ether and chlorinated polyether, etc.; the preferred usage ratio of the conductive carbon material in S1 is 55-65wt%, which includes one or more of carbon black, graphite, carbon fiber, graphene and carbon nanotube, etc.; and the additives in S1 and S2 include one or more of paraffin, polyethylene wax, chlorinated paraffin, polyacrylamide, triethylhexyl phosphoric acid, sodium dodecyl sulfate, methyl amyl alcohol, cellulose derivatives, gur gum and fatty acid polyethylene glycol ester, etc.
[0046] By adopting thermoplastic polymer materials with a melt flow index of 1 to 50 g / 10 min, the fluidity of the intermediate material is improved, which is conducive to uniform extrusion of the material, reduces the generation of defects such as bubbles and impurities, ensures the mechanical strength of the bipolar plate, and thus improves the consistency and quality of the bipolar plate during production; and polyethylene and polypropylene have good processing performance and corrosion resistance. Selecting different thermoplastic polymer materials according to actual needs can not only ensure the processing performance of the bipolar plate, but also enhance its corrosion resistance and mechanical strength, and can also reduce production costs, reduce environmental pollution and waste of resources; the rational use of conductive carbon materials such as carbon black and graphite can not only improve the overall conductivity of the bipolar plate, but also improve the conductive uniformity of the bipolar plate, and by rationally selecting different conductive carbon materials, it can not only balance the conductivity and mechanical properties of the bipolar plate, but also control the production cost, with better practicality and economic benefits. Additives are added when making the raw materials for reaction zone 2. The additives can lubricate, disperse and promote flow, reduce friction and resistance, and improve smoothness during melt extrusion. Additives are added when making the raw materials for anti-corrosion zone 3. The additives can enhance density. Through the action of additives and anti-corrosion fillers, the anti-corrosion performance of anti-corrosion zone 3 is further improved, avoiding the problem of liquid cross-linking in the battery stack due to electrochemical corrosion of the bipolar plates.
[0047] At the same time, the preferred usage ratio of the anti-corrosion filler in S2 is 55~65wt%, which includes one or more of insulating carbon black, white carbon black, carbon fiber and glass fiber; anti-corrosion fillers such as insulating carbon black, white carbon black, carbon fiber and glass fiber have good corrosion resistance, can effectively avoid electrochemical corrosion, extend the service life of the bipolar plate, and improve the overall performance of the battery stack; in addition, by compounding the anti-corrosion filler with thermoplastic polymer materials and additives to form an anti-corrosion zone 3, the integrated production of corrosion protection on both sides of the bipolar plate and conductivity in the middle can be achieved, which greatly simplifies the production process of the bipolar plate, reduces production costs, and improves production efficiency.
[0048] In addition, the internal mixing temperature of the internal mixer in S1 and S2 is 170~250℃, and the internal mixing time is 10~60min. By adopting the internal mixing process with the internal mixing temperature of 170~250℃ and the internal mixing time of 10~60min, it can be ensured that the raw materials such as thermoplastic polymer materials, conductive carbon materials, additives and anti-corrosion fillers are fully mixed in the internal mixer and distributed more evenly, and the temperature of 170~250℃ is conducive to the softening of the raw materials, improving the fluidity, and thus improving the consistency and stability between the raw materials.
[0049] In S4, the barrel zone temperature of the first extruder 6 and the second extruder 6 is 160~200°C, the flow zone temperature is 200~240°C, the distributor temperature is 240~260°C, and the co-extrusion die head 7 temperature is 220~260°C; setting appropriate temperatures according to actual production can improve extrusion efficiency and production efficiency, and can ensure consistency and stability during bipolar plate production.
[0050] When the extruded bipolar plate is calendered by the three-roll calender 8 in S5, the temperatures of the upper, middle and lower rollers in the three-roll calender 8 must be preset in advance, and the set temperature range is 80~150℃, and the preferred temperature range is 100~120℃. After the temperature rises to the preset value, it is kept warm for 30~120min, and the rotation speed of the extruder 6, the three-roll calender 8 and the traction machine 9 is set to 0.5~2m / min, and the preferred rotation speed is 0.8~1.2m / min. Then, in S6, the traction rate of the traction machine 9 and the related distance parameters of the trimmer and the cutter 10 are adjusted according to actual production needs to determine the width and length of the bipolar plate.
[0051] Example 2 The method for preparing the corrosion-resistant integrated composite bipolar plate for a flow battery in this embodiment comprises the following steps: S1: Prepare materials for reaction zone 2: add 25-32wt% of thermoplastic polymer material and 55-62wt% of conductive carbon material in proportion, mix and put into an oven for drying, add into a banbury mixer and then add 1-2wt% of additives to obtain a first intermediate material; S2: Prepare the material for the anti-corrosion zone 3: add 25-32wt% of thermoplastic polymer material and 55-62wt% of anti-corrosion filler in proportion, mix and put into an oven for drying, add into a banbury mixer for banbury mixer, and then add 1-2wt% of additives to obtain the third intermediate material; S3: Crushing and granulating: crushing the first intermediate material and the third intermediate material into granular materials of 2-5 mm in a crusher respectively, removing impurities in the crushed materials through an impurity separator, and obtaining the second intermediate material and the fourth intermediate material respectively; S4: melt extrusion: add the second intermediate material and the fourth intermediate material into the first extruder 6 and the second extruder 6 respectively, the barrel zone temperature is 160-165°C, the flow channel zone temperature is 205-215°C, the distributor temperature is 240-245°C, the co-extrusion die 7 temperature is 225-235°C, and then pass through the co-extrusion die 7 and the three-roll calender 8 to obtain a fully mixed second intermediate material and fourth intermediate material; S5: Co-extrusion molding: After being fully melted, the second intermediate material and the fourth intermediate material enter the co-extrusion die 7 through their respective distributors, are extruded through the lip of the co-extrusion die 7 for thickness and width distribution, and are calendered at the three-roll calender 8 to obtain the fifth intermediate material; wherein the lip thickness of the co-extrusion die 7 is 2-5 mm, the width of the middle area is 300-400 mm, and the width of the two side areas is 100-200 mm; S6: Calendering: The fifth intermediate material is sequentially passed through a traction machine 9, a trimming machine and a cutting machine 10 to obtain an integrated bipolar plate with a required size.
[0052] In summary, the corrosion-resistant integrated composite bipolar plate for liquid flow batteries and the preparation method thereof provided by the present invention realize the integrated production of corrosion protection on both sides of the bipolar plate and conductivity in the middle through co-extrusion technology, which greatly reduces the complexity of the battery stack process and the unstable structural performance of the bipolar plate caused by traditional splicing and bonding, simplifies the liquid flow battery stack production process and the stability of the liquid flow battery, avoids the problem of electrolyte cross-linking caused by electrochemical corrosion, and improves the product quality and service life of the bipolar plate.
Claims
1. A method for preparing a corrosion-resistant integrated composite bipolar plate for a flow battery, characterized in that: The following steps are involved: S1: Prepare the materials for the reaction zone of the bipolar plate: add 10-50wt% of thermoplastic polymer material and 30-70wt% of conductive carbon material in proportion, mix and put into an oven for drying, add into an internal mixer, and then add 0.5-2wt% of additives for internal mixing to obtain a first intermediate material; S2: Prepare the material for the anti-corrosion zone of the bipolar plate: add 10-50wt% of thermoplastic polymer material and 50-70wt% of anti-corrosion filler in proportion, mix and put into an oven for drying, add into an internal mixer, and then add 0.5-2wt% of additives for internal mixing to obtain a third intermediate material; S3: Crushing and granulating: crushing the first intermediate material and the third intermediate material into granular materials of 0-10 mm in a crusher respectively, removing impurities in the crushed materials through an impurity separator, and obtaining the second intermediate material and the fourth intermediate material respectively; S4: Melt extrusion: Add the second intermediate material and the fourth intermediate material into the first extruder and the second extruder respectively, and adjust the temperature of the barrel area, flow channel area, distributor and co-extrusion die of the first extruder and the second extruder to fully melt the second intermediate material and the fourth intermediate material and further mix them evenly; S5: Co-extrusion molding: After being fully melted, the second intermediate material and the fourth intermediate material enter the co-extrusion die through their respective distributors, are extruded through the lip of the co-extrusion die for thickness and width distribution, and are calendered at a three-roll calender to obtain the fifth intermediate material; S6: Sheet forming: The fifth intermediate material passes through a traction machine, a trimming machine and a cutting machine in sequence to obtain an integrated bipolar plate resistant to electrochemical corrosion on both sides.
2. The method for preparing the corrosion-resistant integrated composite material bipolar plate for a flow battery according to claim 1, characterized in that: The melt flow index of the thermoplastic polymer material in S1 is 1 to 50 g / 10 min.
3. The method for preparing the corrosion-resistant integrated composite material bipolar plate for a flow battery according to claim 1, characterized in that: The thermoplastic polymer material described in S1 and S2 includes at least one of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyoxymethylene, carbonate, polyamide, acrylic plastic, polyolefin and its copolymer, polyphenylene ether and chlorinated polyether.
4. The method for preparing the corrosion-resistant integrated composite material bipolar plate for a flow battery according to claim 1, characterized in that: The conductive carbon material in S1 includes at least one of carbon black, graphite, carbon fiber, graphene and carbon nanotubes.
5. The method for preparing the corrosion-resistant integrated composite material bipolar plate for a flow battery according to claim 1, characterized in that: The additives in S1 and S2 include at least one of paraffin wax, polyethylene wax, chlorinated paraffin, polyacrylamide, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, cellulose derivatives, guar gum and polyethylene glycol esters of fatty acids.
6. The method for preparing the corrosion-resistant integrated composite material bipolar plate for a flow battery according to claim 1, characterized in that: The anti-corrosion filler in S2 includes at least one of insulating carbon black, white carbon black, carbon fiber and glass fiber.
7. The method for preparing the corrosion-resistant integrated composite material bipolar plate for a flow battery according to claim 1, characterized in that: The internal mixing temperature of the internal mixers in S1 and S2 is 170-250° C., and the internal mixing time is 10-60 min.
8. The method for preparing the corrosion-resistant integrated composite material bipolar plate for a flow battery according to claim 1, characterized in that: In S4, the barrel zone temperature of the first extruder and the second extruder is 160-200°C, the flow channel zone temperature is 200-240°C, the distributor temperature is 240-260°C, and the co-extrusion die head temperature is 220-260°C.
9. The method for preparing the corrosion-resistant integrated composite material bipolar plate for a flow battery according to claim 1, characterized in that: The lip thickness of the co-extrusion die head in S5 is 2-5 mm, the width of the middle area is 300-400 mm, and the width of the two side areas is 100-200 mm.
10. A corrosion-resistant integrated composite bipolar plate for a liquid flow battery, characterized in that: It comprises a bipolar plate body, wherein the bipolar plate body comprises a reaction zone and an anti-corrosion zone, and the anti-corrosion zone is arranged on both sides along the length direction of the bipolar plate reaction zone.